Assessment of human health risk due to lead in urban park soils using in vitro methods. (April 2021) - Sun, Liu; Ng, Jack C.; Tang, Wenzhong; Zhang, Hong; Zhao, Yu; Shu, Limin
Abstract: Beijing parks always have a large flow of local residents and tourists, and the soil Pb could threaten human health by incidental ingestion. Soil samples from eleven parks in Beijing were collected to assess the human health risk associated with Pb. Lead bioaccessibility in these parks ranged from 3.2 ± 0.4% to 12.1 ± 0.5% in the physiologically based extraction test (PBET) gastric phase and increased when approaching the city center. The chemical forms and soil properties (Fe, organic matter, and grain size) were important factors affecting the soil Pb bioaccessibility. The geo-accumulation index of Beihai Park (BH, near the city center) reached 1.3 ± 0.1 indicating moderate contamination. Lead health risk to children in BH should be of concern though its hazard quotient was below one. Results obtained from the Diffusive Gradients in Thin-films (DGT)-induced fluxes in the soils (DIFS) model showed that Pb-release in some parks farther from the city center was a "partially sustained case" (Rdiff < R < 0.95) indicating that soil particles could partially replenish effective Pb to the soil solution. A relatively higher desorption rate constant (k1 ) and shorter characteristic response time (Tc ) were also found in these parks, indicating non-negligible release risk. Soil Pb based on the PBET method and DIFS model could provide a reliable reference to park managers for the health risk management of Pb pollution. Graphical abstract: Image 1 Highlights: Lead pollution and risk in urban park soils were systematically investigated. In vitro methods were used to assess Pb accumulation and health risk. DIFS model was used to study Pb resupply capacity in urban park soils.